Amaranthus Lycopersicum Juice terhadap Kadar Hemoglobin Ibu Hamil dengan Anemia - Rahayu, Fitria Yulianti; Suryati, Yayat; Murtiningsih, Murtiningsih; Hidayat, Monna Maharani; Maryati, Ida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to identify the effect of giving Amaranthus lycopersicum Juice on increasing hemoglobin in pregnant women with anemia. The method used is a quasi-experimental one-group pretest and repeated posttest design. The results showed a significant effect of Amaranthus lycopersicum Juice intervention on increasing hemoglobin levels in pregnant women with anemia, as evidenced by a p-value of 0.000. In addition, the results obtained based on the GLM-RM analysis showed a significant effect of Amaranthus lycopersicum Juice intervention according to time on increasing hemoglobin levels in pregnant women with anemia, as evidenced by a p-value of 0.000. In conclusion, giving Amaranthus lycopersicum Juice has an effect on increasing hemoglobin in pregnant women with anemia. Keywords: Amaranthus lycopersicum, Anemia, Hemoglobin, Pregnant Women